No tillage in dairy farms: evolution and present situation in Uruguay - Ernst, O.; Siri-Prieto, G.; Bentancur, O.; Carballo, C.; Lazbal, E. (Agrociencia Uruguay, 2007)
A survey carried out in 2000 showed a decreasing stage in the adoption process, predicting a maximum adoption in the 2000-2005 period. In 2005 another survey was carried out with the aim of develop a new analysis of the NT System in dairy farms. Results show a 46% adoption of no till system (58% never till). Dairy farmers doing NT have larger dairy area and productivity. The main problem of the NT was the presence of Poa annua weed, but a decrease of Cynodon dactylon was detected. The lack of NT planters, and soil compaction by grazing were the most important reasons for tilling among NT farmers. The lack of NT planter was the most important reason for no adopting the NT System. Among tillage farmers (no adoption of NT) in 2000, after five years 48% changed to NT System, whereas only 8% of NT farmers in 2000 came back to Tillage System.